Motivasi Belajar pada Remaja Pedagang Asongan yang Bersekolah - Wulandari, Eliza; Hairina, Yulia; Imadduddin, Imadduddin (Sultan Idris Journal of Psychology and Education, 2022)
Learning motivation is something that plays a very important role in the process of seeking knowledge. This study aims to determine the description of learning motivation and the factors that influence learning motivation in teenage hawkers who go to school. This study uses a qualitative method with a phenomenological approach involving three haw kers as participants. The results of the study show that there are two aspects of learning motivation in students who decide to go to school while selling, namely internal encouragement and external encouragement. First, on the aspect of internal encourage ment, there are desires and desires to succeed, encouragement and needs in learning within the subject, and there are hopes and ideals. Second, in the aspect of external encouragement, there are rewards in learning, interesting activities in learning, and there is a conducive learning environment. Factors that influence learning motivation in teenage hawkers are emotional attitudes, stimulation with interesting learning media, affection, and positive reinforcement.